Modern Aspects of the Etiology of Gastric Ulcer and Its Complications (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
the article is devoted to the study of gastric ulcer. Modern data on the etiology and pathophysiological mechanisms of the development of this pathology are considered. A brief review of the literature on this issue was carried out and a clinical case of the development of a complication of gastric ulcer was described.